2013
DOI: 10.1007/978-3-642-40498-6_1
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Evaluation of an Interactive System for Age Related Musculoskeletal Rehabilitation in the Home

Abstract: Abstract. This paper describes a series of user studies carried out to investigate the usability, significance, and acceptance of two visualization tools designed to improve the quality of, and adherence to home-based exercise programmes for musculoskeletal rehabilitation. The core functionality of these visualization tools enabled the users to observe the optimal way to perform their exercises via a mannequin, and receive feedback on their own movements through the use of body worn sensors. Before full deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Studies evaluating virtual environments or human representations (three publications 31,32,36 ) showed potential to promote exercise engagement. Older adults found them motivating, which may be important among older adults who find it difficult to engage in activities due to impaired physical abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating virtual environments or human representations (three publications 31,32,36 ) showed potential to promote exercise engagement. Older adults found them motivating, which may be important among older adults who find it difficult to engage in activities due to impaired physical abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we report on the inertial sensors that we used to overcome the limitations posed by other motion sensing technologies. These sensors were found to be easy to use as well as comfortable for the user to wear [3].…”
Section: Related Workmentioning
confidence: 98%
“…One study was carried out in the laboratory so that the system could be evaluated in a controlled environment. The other study was carried out in participants' homes (the intended environment) [3]. We found that the rehabilitation visualization system enabled the participants to perform the exercises more correctly as they paid attention to the pace, range of movement and the number of repetitions completed.…”
Section: Pilot Usability Studymentioning
confidence: 99%
See 2 more Smart Citations